Brochosomins and other novel proteins from brochosomes of leafhoppers (Insecta, Hemiptera, Cicadellidae). (March 2018) - Rakitov, Roman; Moysa, Alexander A.; Kopylov, Arthur T.; Moshkovskii, Sergei A.; Peters, Ralph S.; Meusemann, Karen; Misof, Bernhard; Dietrich, Christopher H.; Johnson, Kevin P.; Podsiadlowski, Lars; Walden, Kimberly K.O.
Abstract: Brochosomes (BS) are secretory granules resembling buckyballs, produced intracellularly in specialized glandular segments of the Malpighian tubules and forming superhydrophobic coatings on the integuments of leafhoppers (Hemiptera, Cicadellidae). Their composition is poorly known. Using a combination of SDS-PAGE, LC-MS/MS, next-generation sequencing (RNAseq) and bioinformatics we demonstrate that the major structural component of BS of the leafhopper Graphocephala fennahi Young is a novel family of 21–40-kDa secretory proteins, referred to herein as brochosomins (BSM), apparently cross-linked by disulfide bonds. At least 28 paralogous BSM were identified in a transcriptome assembly of this species, most of which were detected in BS. Multiple additional BS-associated proteins (BSAP), possibly loosely attached to the outer and inner surfaces of BS, were also identified; some of these were glycine-, tyrosine- and proline-rich. BSM and BSAP together accounted for half of the 100 most expressed transcripts in the Malpighian tubules of G. fennahi . Except for several minor BSAP possibly related to cyclases, BSM and BSAP had no homologs among known proteins, thus representing taxonomically restricted gene families (orphans). Searching in 50 whole-body transcriptome assemblies of Hemiptera found homologs of BSM in representatives of all five families of the superfamily Membracoidea (Cicadellidae, Myerslopiidae, Aetalionidae, Membracidae, and Melizoderidae), but not in other lineages. Among the identified proteins only BSM were shared in common between all 17 surveyed leafhoppers known to produce BS. Combined CHN elemental and aminoacid analyses estimated the total protein content of BS from the integument of G. fennahi to be 60–70%. Graphical abstract: Image 1 Highlights: Brochosomes are comprised mainly of proteins (60–70%). Their major structural component is a novel family of 21–40 kDa secretory proteins, brochosomins. Brochosomins are taxonomically restricted to Cicadellidae and related families of the hemipteran superfamily Membracoidea. As many as 28 paralogous brochosomins are expressed in one leafhopper species, Graphocephala fennahi. Additional orphan proteins associated with brochosomes were identified.